In-plane shear behaviour of traditional timber walls - Vasconcelos, Graça (2012)
The reconstruction of Lisbon Downtown after the 1755 earthquake was based on a novel constructive system based on masonry buildings with an internal three-dimensional timber-framed structure named "gaiola pombalina". This internal structure aimed at improving the global stability of masonry buildings, enhancing their capacity to dissipate energy under seismic loadings. This paper aims at getting experimental insight on the mechanical behaviour of such timber-framed walls subjected to in-plane loading, as only scarce information is available in literature, in order to assess their effective performance to seismic actions. To do this, the experimental results of cyclic tests carried out on traditional timber-framed walls with distinct typologies will be analyzed, in order to evaluate the failure modes, lateral resistance and energy dissipation; moreover, ahysteretic model will be derived for traditional timber-framed walls. Additionally, the possibility of strengthening the traditional connections of the walls by means of GFRP is also addressed.